Evaluation of the relationship among dental fear, scaling and root planing and periodontal status using periodontitis stages: A retrospective study - Yeungyeung Liu; Caimei Zhang; Jingyi Wu; Huimin Yu; Chengjie Xie (Elsevier, 2022)
Background/purpose: Patients with periodontal disease have higher dental fear levels, which may have negative effects on their clinical outcome during scaling and root planing (SRP). The present study used the new classification of periodontitis and validated questionnaires to assess the relationship among dental fear, SRP pain and periodontal status. Materials and methods: A total of 120 periodontitis patients were enrolled and staging according to the new classification of periodontitis. SRP was performed, and the visual analog scale (VAS) to assess pain was used with every patient after treatment. Questionnaires, including Corah's Dental Anxiety Scale (DAS), Dental Fear Survey (DFS), and short-form Dental Anxiety Inventory (S-DAI) were implemented from the first attendance and subsequent visits after 6 months. The patients were grouped by DAS scores. The statistical analysis was performed using T-test, chi-square, Pearson and Spearman correlative analysis. Results: Compared to pre-SRP treatment, the dental fear level on DFS was decreased in the posttreatment period for all periodontitis stages. There were no statistically significant differences in S-DAI and DAS between pretreatment and posttreatment periods in stage I and II; meanwhile, there were statistically differences in stage III and IV. The correlation among periodontitis stages, VAS and dental fear level was significant. The proportion of high periodontitis stages was increased in high dental fear group. Conclusion: SRP can reduce dental fear levels in all periodontitis stages, especially in stage III and IV. Correlations exist among periodontal status, dental fear and SRP pain. High dental fear is associated with poor periodontal status.